Access control and classifier-based blockchain technology in e-healthcare applications - Maseleno A.; Hashim W.; Perumal E.; Ilayaraja M.; Shankar K. (Elsevier, 2023)
E-healthcare promises to be the next big wave in the healthcare industry, which makes security the most essential component in this framework. Security in sensor network communication is recommended for providing information secrecy and authentication. Many security algorithms are proposed by numerous creators, and among all the security models, Blockchain Technology (BT) with dispersed ledger provides the highest level of security for e-healthcare systems. To improve the security of the healthcare framework, a learning classifier is the support vector machine that is used to characterize sensitive and nonsensitive data from e-healthcare information. After this procedure comes the BT approach, which is connected to protect sensitive data using various layers of encryption, and decryption processes. When the healthcare data are verified, the access-control process considers the reason for authentication. Finally, the simulation results were attained for assessing the performance of the e-healthcare information security model regarding throughput, energy, and security-level measures. 2020 Elsevier Inc. All rights reserved.